2023
DOI: 10.3389/fpsyg.2022.1103925
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of anxiety, depression, and stress among remote learning students during the COVID-19 pandemic: Evidence from a meta-analysis

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has influenced all aspects significantly, and an estimated 1.5 billion students across the globe have been forced to keep up with online courses at home. Many recent empirical studies reported the prevalence of mental health problems among students caused by remote learning during the COVID-19 pandemic, but a few studies aggregated these results. Therefore, to strengthen statistical power, the article aimed to examine the prevalence of anxiety, depression, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
0
13
1
7
Order By: Relevance
“…These findings on the mental health and wellbeing of school teachers and staff complement recent findings in research conducted to assess changes in mental health and wellbeing of students of all ages, due in part to the altered school and social dynamics imposed by pandemic-era adaptations. Both stakeholder groups have demonstrated increases in reports of anxious and depressive symptoms and related diagnoses (39)(40)(41)(42)(43)(44)(45)(46). The pandemic brought many of the issues facing school staff into the broader public discourse and pushed them past the "tipping point, " so to speak, prompting both a mass exodus of teachers and a heightened emphasis on the socioemotional health and needs of both students and teachers, as provided within the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings on the mental health and wellbeing of school teachers and staff complement recent findings in research conducted to assess changes in mental health and wellbeing of students of all ages, due in part to the altered school and social dynamics imposed by pandemic-era adaptations. Both stakeholder groups have demonstrated increases in reports of anxious and depressive symptoms and related diagnoses (39)(40)(41)(42)(43)(44)(45)(46). The pandemic brought many of the issues facing school staff into the broader public discourse and pushed them past the "tipping point, " so to speak, prompting both a mass exodus of teachers and a heightened emphasis on the socioemotional health and needs of both students and teachers, as provided within the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in complete alignment with ours. Dasor et al included students across four universities and revealed elevated stress, anxiety and depression levels at percentages of 60.6%, 66.8% and 42.6%, while a meta-analysis of 20 countries resulted in a prevalence of 58%, 50%, and 71%, respectively [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in the study was on a voluntary basis. The study also had an exploratory component that investigated correlates for wellbeing and mental health among psychology undergraduates during the first restrictive measures in Greece, with the aim to assess specific risk and protective factors in line with current empirical evidence (e.g., Elharake et al, 2022;Fang et al, 2022;Xu and Wang, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…The WHO's report on the impact of COVID-19 pandemic on mental health and wellbeing (World Health Organization, 2022) highlighted the need for developing age-related interventions for young people, especially young adults aged 20-24 years old who were found to be the most severely affected age-group by COVID-19 and the most susceptible population for serious mental health problems. Indeed, previous studies have shown that university students experienced significant psychological distress during the lockdown periods, reporting low levels of resilience (Alyoubi et al, 2021), loneliness (Holm-Hadulla et al, 2021;Werner et al, 2021;Koelen et al, 2022), high levels of stress and anxiety (Charles et al, 2021;Rogowska et al, 2021;Visser and Law-van Wyk, 2021;Elharake et al, 2022;Fang et al, 2022;Xu and Wang, 2023), depression (Kaparounaki et al, 2020;Evans et al, 2021;Volken et al, 2021;Elharake et al, 2022;Fang et al, 2022;Sauer et al, 2022;Xu and Wang, 2023), psychosomatic symptoms (Hadjicharalambous et al, 2021;Silișteanu et al, 2022), alcohol and substance use disorder (Charles et al, 2021;El-Monshed et al, 2021;Prowse et al, 2021), and suicidal thoughts (Wang et al, 2020;Arsandaux et al, 2021).…”
Section: Introductionmentioning
confidence: 99%